Authorship Abu Bakar Ellah di dalam telemovie arahannya - Sydney Thomas, Sibangan (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research is intended to analyse five telemovies directed by Abu Bakar Ellah. The Autuer theory was applied as a conceptual framework in this study. The problem statement of this study was there is no scientific research that has been conducted in the aspects of Abu Bakar Ellah’s directing style. The objectives of this research were to study Abu Bakar Ellah’s backgrounds as a practitioner in the arts and analysing his five telemovies to identify his directing style. The sample of this research was five telemovies directed by Abu Bakar Ellah from the year 2004 until the year 2006, namely ‘PTI’ (2004), ‘Ampal 2: Atek dan Atok’ (2005), ‘Orang Kita 2’ (2006), ‘PTI 2’ (2006), and ‘KDM’ (2006). This study finds that in all of his telemovies, Abu Bakar Ellah consistently repeated aspects of genres, talents, shooting locations, the used of various language, and cultural presentation. Besides that, this study prove that Abu Bakar Ellah only presented the reality of Sabah in his telemovies.